A HIV-infected adolescent with polycystic ovary syndrome - Dejkhamron, Prapai; Unachak, Kevalee; Chhabra, Manik; Oberdorfer, Peninnah (Journal of Pediatric Infectious Diseases, 2011)
We report a case of polycystic ovary syndrome in a 15-year-old human immunodeficiency virus-infected female on highly active antiretroviral therapy who developed hypertriglyceridemia, hyperinsulinemia due to insulin resistance, and hyperandrogenism. Ultrasonography showed multiple small follicles at the right ovary and lobulated follicles at the left ovary. Treatment of polycystic ovary syndrome included insulin sensitizing agents (metformin, pioglitazone) and a contraceptive for hyperandrogenism. We also encouraged life style modification including regular exercise and dietary fat restriction. She attained menarche 1 month after initiation of treatment.
Keywords: PCOS; HIV; HAART